Konseling Qur’ani: Teknik Biblioterapi untuk Kematangan Emosi bagi Warga Binaan Wanita - Yuyun Nuraini; Ahmad Syamsul Muarif (DA'WA: Jurnal Bimbingan Penyuluhan & Konseling Islam, 2025)
The main objective of this study is to find out how the Qur'an is not only the basis for Qur'anic counseling, but its verses can also be applied in bibliotherapy techniques as a medium for self-reflection, development of positive emotions, and psychological recovery for female inmates who are experiencing difficulty in achieving emotional maturity indicators. The method used is a qualitative approach with a case study research design. The results of this study indicate that the Qur'anic counseling approach with bibliotherapy techniques has a positive impact in helping female inmates manage emotional problems. Through the method of reading and contemplating the verses of the Qur'an regularly, inmates experience an increase in emotional balance, inner peace, gratitude, and optimism. The Qur'anic counseling approach using bibliotherapy techniques has a significant role in supporting psychological recovery and the development of emotional maturity of inmates. In addition to functioning as a therapy medium, this method is also a means of self-reflection that strengthens spirituality and mental resilience. With proven significant benefits, this approach is recommended to be applied in coaching programs in correctional institutions to improve psychological well-being and readiness of inmates in the process of social reintegration.